Salvage surgery after definitive chemoradiotherapy for patients with non-small cell lung cancer - Hamada, Akira (Transl Lung Cancer Res, 2021)
Definitive chemoradiotherapy (CRT) has been a standard of care for patients with unresectable stage III non-small cell lung cancer (NSCLC). However, locoregional recurrence occurs in about 30% of patients after definitive CRT. Recently, the addition of durvalumab as maintenance therapy has shown to improve the outcome of these patients. However, locoregional recurrence will still remain. “Salvage surgery” has been performed to achieve local control in clinical practice, although its clinical significance is unclear. In this review, we define salvage surgery as lung resection for local control of the tumor which was not planned initially, after failure or insufficient treatment effect of the initial CRT for locally advanced cancer and evaluated nine studies to gain some insights on its role in the treatment of lung cancer. The time from radiotherapy (RT) to salvage surgery varied considerably (range, 3 to 282 weeks). Salvage surgery was performed for persistent disease (47%) and locoregional recurrence (52%). Lobectomy (63%) and mediastinal lymph node dissections (90%) were the most common procedures. However, the rate of pneumonectomy was higher in salvage surgery (28%) compared to that in lung resection in general. The median morbidity was 41% (range, 15% to 62%) and the mortality was 4% (range, 0 to 11%) which appeared acceptable. The median recurrence-free survival and overall survival (OS) after salvage surgery ranged from 10 to 22 months and 13 to 76 months, respectively. Favorable prognostic factors of salvage surgery were longer period from RT to salvage surgery and radiological downstaging. The pathological response was also prognostic, although this information cannot be obtained preoperatively. We conclude that salvage surgery can be considered especially for those with late local recurrence or those with the metabolic response. Given the condition where phase III trials are difficult, the accumulation of real-world evidence in a prospective fashion will be necessary.